The Correlation Between the Set of Mental Functions and Emotion Recognition Skills Formation in Children with Autism Spectrum Disorder - K.K. Mesnyankina; A.I. Sarelaynen; S.I. Anishchenko; K.B. Kalinin (Moscow State University of Psychology and Education, 2020)
Research is devoted to revealing the relation of the complex of mental functions and their components with the ability to recognize emotions from facial expressions and with the success of learning this skill in children with autism spectrum disorder (ASD). The set includes characteristics of the visual perception, properties of attention, properties of thinking and visual spatial analysis and synthesis. The study involved 19 children with ASD at the age of 6 to 12 years, including 2 girls and 17 boys. The training consisted of 12 sessions. Research showed that the success of emotion recognition from facial expressions in children with ASD associated with the level of development of visual spatial analysis and synthesis. It is also revealed that the success of emotion recognition training is connected with the level of development of visual spatial analysis and synthesis, abstract reasoning, and a concept formation.